EDUKASI DAN PENDAMPINGAN MUDA MUDI DALAM PENCEGAHAN PENYALAHGUNAAN NARKOBA - Kusyanti, Florentina (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2024)
The era is getting more advanced and modern, but this significant change will also affect young people's behavior, mentality, and morals. Nowadays many young people are trying to get rid of pressure, stress, and feeling cold by drinking. Initially drinking normally but because it doesn't affect enough, the drink will be mixed with sleeping pills or something else. This drug has entered the villages, so parents and teachers must be more vigilant because the drugs are not sold separately but are usually included in candy or bread which are packaged attractively. So it is essential that elementary, middle, and high school children, in Karang Taruna need to get education and assistance in preventing drug abuse. The purpose of community service is to increase knowledge and make people aware of the dangers of drugs for teenagers, young people, and parents. The methods used in this service are counseling, education, counseling for parents and teenagers who have problems, and assistance for teenagers and young people who have used it. The results of community service were that the participants who came were 70 people consisting of (youth, youth, and youth companion, counseling lasted 60 minutes, and question and answer lasted 60 minutes, the participants were very enthusiastic about participating in this activity so after the material was finished the young people were very enthusiastic to ask questions and when the question sheet was given many young people wanted to answer.